Charles Darwin i dansk litteratur med særlig henblik på Johannes V. Jensens forfatterskab - Rossel, Sven Hakon (Folia Scandinavica Posnaniensia, 2016)
Charles Darwin’s theories were already introduced in Scandinavia in the early 1860s, whereas his two major works, On the Origin of Species (1859) and The Descent of Man (1871), were translated by Danish writer J.P. Jacobsen in the 1870s. Jacobsen acts as an important intermediary both as a scientist and, probably, the first Danish writer whose work is influenced by Darwin’s thoughts. But also in the writings of other authors of the time, e.g. Herman Bang, at least the name ”Darwin” infrequently occurs as is also the case with the symbolist writers of the 1890s, e.g. Viggo Stuckenberg and Sophus Claussen. However, not until after 1900 does Darwin serve as an artistic inspiration and a positive role model. This happens in an overpowering manner in the fictional and essayist works of the Danish Nobel Prize-winner Johannes V. Jensen. Jensen’s Darwinism was not countered until the so-called ”livsanskuelsesdebat” – a philosophical debate – during the 1920s with the eloquent poet and dramatist Helge Rode as his acute opponent. Hereafter, Darwin’s role in Danish literature decreases significantly unless one wishes to see Peter Høeg’s novel from 1996, Kvinden og aben (The Man and the Ape) as the last example of a Darwin-influence on a literary text.